In silico characterization of chitin deacetylase genes in the Diaphorina citri genome - Sherry Miller (GigaScience Press, 2021)
Chitin deacetylases (CDAs) are one of the least understood components of insect chitin metabolism. The partial deacetylation of chitin polymers appears to be important for the proper formation of higher order chitin structures, such as long fibers and bundles, which contribute to the integrity of the insect exoskeleton and other structures. Some CDAs may also be involved in bacterial defense. Here, we report the manual annotation of four CDA genes from the Asian citrus psyllid, Diaphorina citri, laying the groundwork for future study of these genes.